ON THE OCCASION OF THE 120TH ANNIVERSARY OF PROFESSOR I.I. ELKIN - Briko, N.I.; Sokolova, T.V.; Matnazarova, G.S. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2024)
The life way and career of a well-known Russian epidemiologist, Health care organizer, public figure, authoritative scientist and pedagogue Professor I.I. Elkin have been presented in the article.